(untitled) (Journal of Economic Research & Business Administration, 2017)
This article deals with the revision of the state of sustainable development in the Republic of Kazakhstan. The main patterns and problems are overviewed, also some forecast and recommendations are given by the author. The relevance of the work consists in analyzing the correlation of the positions of the theory and conceptual principles with real practice implementation of corporate program. Applied to the Kazakhstani practice issues of institutionalization of the notion of corporate social responsibility in the business and political environment, as well as highlighted the most important factors of decision-making in the field of corporate responsibility in corporate sector. With the use of primary and secondary data, the sustainable development is assessed by the 3 main categories. During the paper, some statistics is given, as well as the world practices and benchmarks.